True or False?
For positive reals a , b , c ,
( a b ) c = ( a c ) b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sidenote: Be careful with the parenthesis (brackets). The expression a b c is not necessarily equal to a c b .
Assuming a=1 b=2 and c=3
(1^2)^3 = 8 (1^3)^2 = 9
This is not always true. Brackets always come first. Incorrect answer
Log in to reply
dude 1 ^ 2 = 1 . I think you wanted to say 2 ^2 ^3
Zach, it is true that brackets come first. Even with your hypothetical values for a, b, and c, this equation holds true.
For the left side, doing brackets first: 1^2 = 1. Then, doing exponents: 1^3 = 1. For the right side, doing brackets first: 1^3 = 1. Then, doing exponents. 1^2 = 1.
1 = 1. This is always true. Correct answer.
(a^b)^c=a^(b c) (a^c)^b=a^(c b) on comparing powers b c=c b
(a^b)^c =a^b×c (a^c)^b= a^c×b
(a^b)^c = a^bc & (a^c)^b =a^cb Therefore (a^b)c =(a^c)b
communtative property bxc=cxb
Problem Loading...
Note Loading...
Set Loading...
( a b ) c = a b × c
( a c ) b = a c × b
By the commutative property of multiplication, b × c = c × b Therefore, ( a b ) c = ( a c ) b